Delivering Simulation Activities Safely: What if We Hurt Ourselves?. Issue 1 (February 2021) - Naweed, Anjum; Dennis, Diane; Krynski, Ben; Crea, Teresa; Knott, Cameron
Abstract : Summary Statement: Although a focus on the learner rightly remains in any teaching environment, the psychological safety of everyone involved in the conduct of experiential learning and critical academic scholarship is important. Education literature suggests that faculty are just as prone to psychological harm as their learners. This commentary describes adverse experiences from a simulation-based education event that took place at an Australasian interprofessional and cross-domain simulation workshop. Event facilitators explored the notion of the "safe container" but, in the process, were themselves exposed to psychological injury. We summarize an ostensibly complex simulation activity with unintended sequelae, the ethical concerns surrounding the faculty care, and from lessons learned, present an extended conceptualization of the safe container including broader parameters around the preparation of all involved in the delivery of simulation-based activities. Our goals in sharing this case is to encourage the community to become more vigilant regarding the unintended consequences of our simulation activities and to encourage open reporting and discussion of such incidents for the betterment of the field.